2020
DOI: 10.1002/ece3.6593
|View full text |Cite
|
Sign up to set email alerts
|

Skull shape of a widely distributed, endangered marsupial reveals little evidence of local adaptation between fragmented populations

Abstract: The biogeographic distribution of diversity among populations of threatened mammalian species is generally investigated using population genetics. However, intraspecific phenotypic diversity is rarely assessed beyond taxonomy‐focused linear measurements or qualitative descriptions. Here, we use a technique widely used in the evolutionary sciences—geometric morphometrics—to characterize shape diversity in the skull of an endangered marsupial, the northern quoll, across its 5,000 km distribution range along Nort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 97 publications
0
10
0
Order By: Relevance
“…Woolley et al (2015) and Hohnen et al (2016b) found that the Northern Territory and Kimberley northern quoll populations are genetically divergent, and How et al (2009) found the same for Kimberley and Pilbara populations. The results of more recent morphological examinations are mixed: Umbrello (2018) found significant differences in skull size, dentition, and external characteristics between Queensland, Northern Territory, Kimberley, and Pilbara populations, whereas Viacava et al (2020) found few consistent differences. Some island populations separated from the mainland by permanent sea channels (Bigge, Boongaree, Koolan), as well as less permanent channels (Dolphin Island) also appear genetically divergent from mainland populations (How et al 2009;Spencer et al 2017;Chan et al 2020).…”
Section: Taxonomy and Geneticsmentioning
confidence: 99%
“…Woolley et al (2015) and Hohnen et al (2016b) found that the Northern Territory and Kimberley northern quoll populations are genetically divergent, and How et al (2009) found the same for Kimberley and Pilbara populations. The results of more recent morphological examinations are mixed: Umbrello (2018) found significant differences in skull size, dentition, and external characteristics between Queensland, Northern Territory, Kimberley, and Pilbara populations, whereas Viacava et al (2020) found few consistent differences. Some island populations separated from the mainland by permanent sea channels (Bigge, Boongaree, Koolan), as well as less permanent channels (Dolphin Island) also appear genetically divergent from mainland populations (How et al 2009;Spencer et al 2017;Chan et al 2020).…”
Section: Taxonomy and Geneticsmentioning
confidence: 99%
“…disparity) in comparison to placentals [5,6]. This hypothesis has been extensively debated in the literature, and previous authors have found contrasting results [7,12,13,[16][17][18][19]. Furthermore, some studies have argued that other factors may have impacted mammalian evolution, such as historical biogeographic distributions [18].…”
Section: Introductionmentioning
confidence: 99%
“…Early collections of northern quolls, led Thomas (1926) to recognize four distinct forms, including Dasyurus hallucatus hallucatus , D. h. nesaeus , D. h. exilis and D. h. predator , with type localities from the Top End (NT), Groote Eylandt (NT), eastern Kimberley (WA) and Cape York (QLD), respectively (Mahoney & Ride, 1988). These subspecies have not been recognized by subsequent authors due to the apparent lack of distinct morphological differentiation (Jackson & Groves, 2015; Oakwood, 2008; Viacava et al, 2020), despite molecular evidence of two to four divergent lineages (Firestone, 2000; Woolley et al, 2015). Here, we present data showing strong hierarchical population structuring of these divergent lineages, which conforms to the disjunct nature of the northern quoll distribution across the continent.…”
Section: Discussionmentioning
confidence: 99%